Impact of European Law on Occupational Health and Safety Provisions - Sierocka, Iwona (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The subject of considerations is the importance of EU regulations, especially Directive 89/391 EEC as for Polish regulations in the area of occupational health and safety. In the article, the author concentrates on the regulations governing the legal consultation with workers, or their representatives, on OHS matters. According to the Polish Labor Code, the consultations both on the workers’ and employers’ part are universal. This is because they include all workers and all employers. The subject of the legal consultations are all activities related to occupational health and safety. The Polish Labor Code provides guarantees that workers and their representatives will not suffer any negative consequences for performing consultative functions. In the author’s opinion, Polish regulations in the area of occupational health and safety fully implement the provisions of Directive 89/391/EEC.